Impact of nasogastric tube exclusion after minimally invasive esophagectomy for esophageal cancer: a single-center retrospective study in India - Vignesh N; Vaibhav Kumar Varshney; Selvakumar B; Subhash Soni; Peeyush Varshney; Lokesh Agarwal (Journal of Minimally Invasive Surgery, 2024)
Purpose: This study examines the impacts of omitting nasogastric tube (NGT) placement following cervical esophagogastric anastomosis (CEGA) in Enhanced Recovery After Surgery (ERAS) protocols, comparing outcomes to those from early NGT removal. Methods : In a retrospective cohort of esophagectomy patients treated for esophageal cancer, participants were divided into two groups: group 1 had the NGT inserted post-CEGA and removed by postoperative day 3, while group 2 underwent the procedure without NGT placement. We primarily investigated anastomotic leak rates, also analyzing hospital stay duration, pulmonary complications, and NGT reinsertion. Results : Among 50 esophageal squamous cell carcinoma patients, 30 in group I were compared with 20 in group II. The baseline demographic and tumor characteristics were similar between both groups. The overall incidence of anastomotic leak was 14.0%, comparable in both groups (16.7% vs. 10.0%, p = 0.63). The postoperative hospital stay was significantly shorter in the no NGT group (median of 7 days vs. 6 days, p = 0.03) with similar major morbidity (Clavien-Dindo grade ≥IIIa; 13.3% vs. 5.0%, p = 0.63). There was no 30-day mortality, and one patient in each group had reinsertion of NGT for conduit dilatation. Conclusion : The exclusion of an NGT across CEGA after esophagectomy did not influence the anastomotic leak rate with comparable complications and a shorter hospital stay.